2012
DOI: 10.1098/rstb.2011.0392
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neuropathic-pain-related behaviour by the spinal endocannabinoid/endovanilloid system

Abstract: Neuropathic pain refers to chronic pain that results from injury to the nervous system. The mechanisms involved in neuropathic pain are complex and involve both peripheral and central phenomena. Although numerous pharmacological agents are available for the treatment of neuropathic pain, definitive drug therapy has remained elusive. Recent drug discovery efforts have identified an original neurobiological approach to the pathophysiology of neuropathic pain. The development of innovative pharmacological strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 144 publications
(193 reference statements)
0
41
0
1
Order By: Relevance
“…However, among the pharmacological strategies under investigation, endocannabinoids and endovanilloids (that is, endogenous agonists at TRPV1 channels), in addition to enzymes that regulate their metabolism, represent a promising therapeutic avenue to a successful pain treatment. In a timely fashion, Starowicz & Przewlocka [37] update the relationship between CB1 receptors and TRPV1 channels and their possible implications for neuropathic pain, taking into consideration endogenous spinal mechanisms of pain control by anandamide, and the current and emerging pharmacotherapeutic approaches that benefit from the pharmacological modulation of spinal endocannabinoid and/or endovanilloid systems under chronic pain conditions. Emerging data suggest that the potential therapeutic effects of endocannabinoids can be strengthened by modulating their endogenous tone, i.e.…”
Section: The Many Facets Of Endocannabinoidsmentioning
confidence: 99%
“…However, among the pharmacological strategies under investigation, endocannabinoids and endovanilloids (that is, endogenous agonists at TRPV1 channels), in addition to enzymes that regulate their metabolism, represent a promising therapeutic avenue to a successful pain treatment. In a timely fashion, Starowicz & Przewlocka [37] update the relationship between CB1 receptors and TRPV1 channels and their possible implications for neuropathic pain, taking into consideration endogenous spinal mechanisms of pain control by anandamide, and the current and emerging pharmacotherapeutic approaches that benefit from the pharmacological modulation of spinal endocannabinoid and/or endovanilloid systems under chronic pain conditions. Emerging data suggest that the potential therapeutic effects of endocannabinoids can be strengthened by modulating their endogenous tone, i.e.…”
Section: The Many Facets Of Endocannabinoidsmentioning
confidence: 99%
“…Firstly, systemic URB597 treatments resulted in effects highly similar to those obtained here with prefrontal URB597 implants, and these effects were abolished by the CB1 antagonist AM251 (Haller et al 2013). Secondly, TRPV1 receptors -in contrast to CB1 receptors-appear to be downregulated by the chronic enhancement of anandamide signaling; moreover, the antinociceptive effects of chronic FAAH inhibition were attributed to the desensitization of this receptor Ross 2003;Schlosburg et al 2010;Starowicz and Przewlocka 2012). These considerations suggest that the effects reported here were primarily mediated by the CB1 and not by the TRPV1 receptor.…”
Section: Comparisons With Earlier Findings and Putative Mechanismsmentioning
confidence: 73%
“…When co-expressed, CB1 agonists suppressed TRPV1 activation through dephosphorylation, increasing the threshold level for agonists (47). Pharmacological elevations of AEA in an arthritic rat were shown to suppress hypersensitivity of afferent nociceptors and elevated pain thresholds by a process containing CB1 and TRPV1 channels (15). This mechanism was confirmed through the use of joint blood flow experiments, which demonstrated that the vasomotor effects of a CB1 agonist in rat knees could be inhibited by TRPV1 antagonism (53).…”
Section: Changes In Trp Stimulationmentioning
confidence: 82%
“…In a similar study, URB597 suppressed inflammatory hyperemia in a mouse model of acute arthritis (64). In the periphery, FAAH inhibition mediates anti-inflammatory effects by down regulating cytokine production and the desensitization of TRPV1, resulting in analgesia (15). Inhibition of AEA catabolism is said to have promising effects in the management of OA pain mediated by both anti-inflammatory (65) and anti-hyperalgesia actions (62).…”
Section: Was Shown That Aea Can Inhibit Tnf-α-induced Nf-κβ Activatiomentioning
confidence: 98%
See 1 more Smart Citation